THE RELATIONSHIP OF WORK MOTIVATION WITH NURSE PERFORMANCE - Dian Dwiana Maydinar; Buyung Keraman; Eti Lestati (Homes Journal = Hospital Management Studies Journal, 2021)
Background: Performance is the result of work achieved by a person or group of people in an organization according to their authority and responsibilities. Good performance can be achieved by increasing work motivation. The higher a person's work motivation, the higher the performance produced. Objective : To analyze the relationship between Work Motivation and Performance in Inpatient Room Melati and Seruni Hospital Dr. M. Yunus Bengkulu.Method: This study uses survey analytic with cross sectional design. Population in this study were all nurses at Inpatient ward of Melati and Seruni, Dr. M. Yunus Bengkulu Hospital, with the amount of 43 nurses. Data analysis techniques were performed by univariate and bivariate analysis with the Spearmen Rank Test.Result: this study are based on the Spearmen Rank Test obtained significance value (sig) of 0.220 with p-value = 0.156. Conclusion: Because the value of p> 0.05, it can be concluded that there is no significant relationship between Work Motivation with Nurses Performance at Inpatient ward of Melati and Seruni, Dr. M. Yunus Bengkulu Hospital.